Effects of Social Support Toward Working Stress of The Nurses of X Hospital - Anggraini, Irmawa Puspita; Nanda, Danan Prima (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Nurse has essential role to provide health care for public. When the nurse has demands of work more increasing, it causes arising stress. This study aims to find out the effects of social support toward work stress. This study is conducted to the 30 intensive care ICU and ICCU nurses who is consisted of 11 males and 19 females. As a result, the calculation result indicates that p-value 0.006 < 0.05 so that it can be inferred that the effects of social support of work stress toward work stress of nurses in X hospital.